Effect of Heat Treatment on Tensile Properties of Deposited Metal from a New Nitrogen-Containing Nickel-Based Flux-Cored Welding Wire - Yingdi Wang; Yunhai Su; Yingdong Wang (Crystals)
This study uses a new type of nitrogen-containing nickel-based flux-cored welding wire to study the microstructure and tensile properties of the deposited metal at 600 –700 °C. The results indicate that the precipitation phases of deposited metal mainly include the M (C, N) phase, Laves phase, and γ′ phase. After solution and aging treatment, the Laves phase remelts into the substrate. Nano-sized M (C, N) phase particles precipitate inside the grains, while the M23C6 phase forms at the grain boundaries. When stretched at 600 °C, the main deformation mechanism of the as-welded specimen is the cutting of precipitated phases by a/2<110> unit dislocations. The ultimate tensile strength of the heat-treated sample is much higher than that of the as-welded sample, but the ductility is reduced. The deformation mechanism involves not only the a/2<110>matrix dislocation cutting precipitation phase, but also two a/6<121>incomplete dislocation cutting precipitation phases together to form stacked dislocations. When stretched at 700 °C, dislocation loops appeared in the SA sample, indicating that the dislocation bypass mechanism had been activated. The tensile deformation mechanism of the deposited metal achieved a transition from dislocation cutting precipitated phases to dislocation bypassing precipitated phases.